Financial Management Information System Design Using the Scrum Method (Case Study: CV Kurnia Jaya) - Aldian Aji Kusuma (Universitas Muhammadiyah Sidoarjo, 2021)
Along with the development of the era of technology is also increasingly advanced. All companies are starting to compete to have technology to help their companies. No exception in managing finances, all companies also apply technology in recording their finances. The financial management information system is one of the information systems that can make it easier to manage company finances. The purpose of this study is to help CV Kurnia Jaya companies manage their finances by designing a financial management information system that can ease the work of employees in the company's finance department. By using the scrum method, application development time becomes more flexible. This research produces a design or prototype of a financial management information system that can be used or developed again in the future. The results of the temporary prototype can be used by CV Kurnia Jaya to help manage their finances. The app has also undergone its first phase of testing using closed beta testing. Based on the results of closed beta testing conducted by researchers of financial management information systems, an average of 83.9% was obtained for functional testing